Perancangan Video Pembelajaran Berbasis Filmora pada Mata Pelajaran IPS Kelas VIII di SMPIT Cahaya Hati - Febrianto‎, Febrianto‎; Supriadi, Supriadi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The current generation, including millennials, the dominant way of learning is kinesthetic-based, in the new normal learning, video media is one of the audio-visual media, where this media combines several human senses, students not only listen to what the teacher explains. only but also see what facts the teacher presents in the media‎ . The results of the interview with Ustazah Dila on April 19, 2021, he said that in the learning process he still uses the lecture, discussion, and group method. The learning media used during learning still use printed books and modules. The methods and media used are still not effective, the lecture, discussion and discussion methods tend to be monotonous and so the group has aneffect on the enthusiasm of students to learn. Based on this, the solution that was given was by designing a learning video. The research method uses the Research and Development (R&D) method. The system development model uses Luther Sutopo's Multimedia Development Life Cycle development model, which consists of 6 stages: Concept, Design, Material Collection, Assembly, Testing, and Distribution. The product tests used in this research are the validity test, practicality test, and effectiveness test. The resultsof the product test that the author did obtained a validity test from 4 experts got a score of 0.86 with very valid category, practicality test from 5 people practicums got a value of 0.97 with a very high category, and a teacher effectiveness test with a value 0.88 and from 5 students with a value of 0.95 with a very effective category.